2012
DOI: 10.1016/j.juro.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties and Associated Collagen Composition in Vaginal Tissue of Women with Pelvic Organ Prolapse

Abstract: The scanning haptic microscope produced reliable mechanical measurements in small tissue samples without tissue destruction. Vaginal wall tissues are stiffer in women with pelvic organ prolapse than in controls. This vaginal wall stiffness was associated with lower protein expression of collagen III in the vaginal wall compared to that in asymptomatic controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 28 publications
5
47
0
2
Order By: Relevance
“…[30][31][32][33][34] Recently, Zhou et al, 30 found decreased collagen III expression (and reduced tissue elasticity) in fullthickness samples of vaginal tissue from patients with prolapse. Previous biomechanical study has also demonstrated that women with prolapse have stiffer vaginal tissues.…”
Section: Studies Of Collagen Composition In Vaginal Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33][34] Recently, Zhou et al, 30 found decreased collagen III expression (and reduced tissue elasticity) in fullthickness samples of vaginal tissue from patients with prolapse. Previous biomechanical study has also demonstrated that women with prolapse have stiffer vaginal tissues.…”
Section: Studies Of Collagen Composition In Vaginal Wallmentioning
confidence: 99%
“…[20][21][22] Several studies have compared the amount of total and individual subtypes of collagen in the supporting ligaments and vaginal tissue of women with POP to a control group (see Table 1). 19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 Current anatomical considerations for prolapse. Level 1: The upper 1/3 of the vagina is suspended to the pelvic wall by the uterosacral and cardinal ligaments, condensations of endopelvic fascia.…”
Section: Collagen Compositionmentioning
confidence: 99%
“…Researchers have mainly focused on characterizing the extracellular matrix (ECM) of connective tissue that support the pelvic floor, such as the vaginal wall [2, 711], the uterosacral ligaments [12, 13], and the pubocervical fascia [13, 14]. Different outcomes have been reported, but the overall consensus is that the connective tissue of the vaginal wall is abnormal in women with POP [15].…”
Section: Introductionmentioning
confidence: 99%
“…Partindo do intuito de associar uma deficiência na composição do colágeno no tecido vaginal de mulheres, dividiram-nas em três grupos: grupo controle pré-menopausa (n= 2-5), grupo pré-menopausa com POP (n= 1-5) e grupo menopausa com POP (n= 3-12) e avaliaram a rigidez tecidual da parede vaginal anterior e posterior dos casos em menopausa (31.00±23.62 e 40.31±44.47, respectivamente) e casos em pré-menopausa (18.51±15.07 e 22.37±8.50, respectivamente), que demonstrou valor significativamente maior que aquela do grupo controle (-0.66±7.05 e -0.66±7.05, respectivamente), indicando que o tecido mais rígido está associado com o POP. Não houve diferença estatística na expressão da proteína de colágeno tipo I, porém, apontando que a proteína de colágeno tipo III, no tecido do grupo controle foi maior do que nos casos de menopausa anterior (13) . Objetivando investigar a relação entre a hipermobilidade articular, prolapso geniturinário e a recorrência em mulheres, um total de 43 mulheres concordou com o estudo e foram divididas em dois grupos, baseados na prevalência de hipermobilidade articular.…”
Section: Resultsunclassified
“…Sabe-se que o tecido conectivo dos ligamentos de suporte da parede vaginal é formado por matriz extracelular (MEC), que possui maior predomínio de componentes fibrilares (colágeno e elastina). O colágeno é considerado um fator determinante para as propriedades biomecânicas do tecido, por proporcionar uma resistência ao alongamento (13) . A MEC está em constante remodelação, equilíbrio de síntese e degradação, na qual os fibroblastos são os principais sintetizadores de colágeno tipo I e III e as enzimas metaloproteinases (MMP) são responsáveis em degradar o colágeno.…”
Section: Introductionunclassified